Bhineka Tunggal Ika and Hasbi ash-Shiddieqy’s Indonesian Moderate Fiqh - Engkos Kosasih; Muhammad Al Mighwar; Makmur Harun; Akhmad Najibul Khairi Syaie; Sulaiman Dorloh (TSAQAFAH, 2024)
Before Hasbi ash-Shiddieqy, Indonesian fiqh was predominantly characterized by a rigid and blind imitation (taqlid) rigidly adopting interpretations from Islamic schools in regions such as the Hijaz, Egypt, and India. These foreign teachings often lacked relevance to Indonesia’s cultural context, causing friction between Islamic jurisprudence and local customary law (hukum adat). In response, Hasbi developed an Indonesian fiqh that integrated local traditions, aligning with the national motto Bhineka Tunggal Ika, which UN Secretary-General Antonio Guterres praised as crucial for a harmonious future in Southeast Asia. This approach fosters unity through the respectful recognition of cultural diversity. This study explores how sustaining Bhineka Tunggal Ika can be achieved through religious moderation based on Indonesian fiqh, particularly focusing on Hasbi ash-Shiddieqy. Employing qualitative research, the study utilized a literature review and thematic content analysis through four steps: data collection (gathering relevant information), data reduction (filtering out irrelevant data), data display (visually organizing key themes), and inference (synthesising findings to address research questions). This study reveal that Hasbi ash-Shiddieqy’s Indonesian fiqh approach strengthens religious moderation by integrating universal Islamic principles with local traditions and promoting peaceful conflict resolution, while being consistent with national regulations-Presidential Regulation 58/2023 and Minister of Religion Regulation 3/2024-that promote unity in diversity and foster social cohesion in Indonesia. Therefore, Hasbi ash-Shiddieqy’s Indonesian fiqh modernizes Islamic law by integrating maslahah (public welfare) and urf(cultural practices), moving beyond rigid taqlid, and deserves recognition as a vital source for strengthening religious moderation and sustaining Bhineka Tunggal Ika in Indonesia.